Théorie des modèles de textes appliquée à la traductologie - Tomaszkiewicz, Teresa (Wydawnictwo Naukowe UAM, 2001)
The article describes the connection between the science of translation and contrastive textology. The foucs is on the texts of a strictly determined fixed structure, such as: instructions of use, bank or medical leaflets, recipes, job advertisements, legislative texts (a company establishment agreement, a leasing agreement, etc.), which translators may be exposed to in their professional careers. The article tries to outline these texts’ models, which tend to function parallelly in different societies as a basis for their correct translation.
The theory of texts’ models applied in the science of translation